Juridical Aspects of Violation of Authotiry by Dental Handyman - Subhi, Imam; Darmawan, Didit; Khayru, Rafadi Khan; Suwito, Suwito; Mujito, Mujito (Bulletin of Science, Technology and Society, 2023)
Dental handyman practices in Indonesia are a popular healthcare alternative, especially for low-income people. However, violations of authority by dental handyman, such as dental installation that hasn't comply the standard, create significant health risks for consumers. This study analyzes the juridical aspects related to these violations based on Law Number 8 Year 1999 on Consumer Protection and Minister of Health Regulation Number 39 Year 2014. This research uses a normative juridical approach with data from legal literature, laws and regulations, and official documents. The results show that the illegal practice of dental handyman is influenced by weak supervision, lack of understanding of regulations, and low consumer awareness. The government needs to strengthen regulations, improve supervision, and provide education to the communities to reduce the risks of the practice. Recommendations include developing training for dental handyman, more strict law enforcement, and consumer awareness socialization.